Probing the diagnostic values of plasma cf-nDNA and cf-mtDNA for Parkinson’s disease and multiple system atrophy - Ying, Chao; Li, Yuan; Zhang, Hui; Pang, Shimin; Hao, Shuwen; Hu, Songnian; Zhao, Lifang (Frontiers in Neuroscience, 2024)
BackgroundCell loss and mitochondrial dysfunction are key pathological features of idiopathic Parkinson’s disease (PD) and multiple system atrophy (MSA). It remains unclear whether disease-specific changes in plasma circulating cell-free nuclear DNA (cf-nDNA) and mitochondrial DNA (cf-mtDNA) occur in patients with PD and MSA. In this study, we investigated whether plasma cf-nDNA, cf-mtDNA levels, as well as cf-mtDNA integrity, are altered in patients with PD and MSA.MethodsTaqMan probe-based quantitative PCR was employed to measure plasma cf-nDNA levels, cf-mtDNA copy numbers, and cf-mtDNA deletion levels in 171 participants, including 76 normal controls (NC), 62 PD patients, and 33 MSA patients. A generalized linear model was constructed to analyze differences in circulating cell-free DNA (cfDNA) biomarkers across clinical groups, while a logistic regression model was applied to assess the predictive values of these biomarkers for developing PD or MSA. Spearman correlations were used to explore associations between the three cfDNA biomarkers, demographic data, and clinical scales.ResultsNo significant differences in plasma cf-nDNA levels, cf-mtDNA copy numbers, or cf-mtDNA deletion levels were observed among the PD, MSA, and NC groups (all P > 0.05). Additionally, these measures were not associated with the risk of developing PD or MSA. In PD patients, cf-nDNA levels were positively correlated with Hamilton Anxiety Rating Scale scores (Rho = 0.382, FDR adjusted P = 0.027). In MSA patients, cf-nDNA levels were positively correlated with International Cooperative Ataxia Rating Scale scores (Rho = 0.588, FDR adjusted P = 0.011) and negatively correlated with Montreal Cognitive Assessment scores (Rho = −0.484, FDR adjusted P = 0.044). Subgroup analysis showed that PD patients with constipation had significantly lower plasma cf-mtDNA copy numbers than those without constipation (P = 0.049). MSA patients with cognitive impairment had significantly higher cf-nDNA levels compared to those without (P = 0.008).ConclusionPlasma cf-nDNA level, cf-mtDNA copy number, and cf-mtDNA deletion level have limited roles as diagnostic biomarkers for PD and MSA. However, their correlations with clinical symptoms support the hypothesis that cell loss and mitochondrial dysfunction are involved in PD and MSA development.